(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In optoelectronic applications Cadmium Sulfide have very good substance. Which creates interest to describe its optical studies in nanoscale range? Presently photoluminescence of CdS/PVK nanocomposites have been reported. Chemical method is used to prepare the composites and characterized them XRD, UV-Visible absorption and study their photoluminescence. The study of XRD indicates CdS nanocrystals formation having cubic zinc blend crystal structure, with three peaks of planes are respectively 111, 220, and 311. Size of particle is calculated using DebyScherrer’s technique. It has obtained within 3 to 12 nm. Results from XRD shows that when CdS concentration is increases in PVK the particle size also increases. The optical absorption spectra of the nanocomposites show blue shifted absorption edge which show increased band gap because of quantum confinement effect. Absorption side is shifted on larger wave length shows reducing the band gap with increasing CdS concentration, which indicates increase in particle size. The wavelength of 400 nm is incident on PVK, photoluminescence (PL) exhibit single peak on 451 nanometer and covers spectral range from 400 to 600 nm. The CdS nanocrystals give single peak at 530 nm when excited separately by 400 nm. In CdS/PVK nanocomposites two PL peaks are obtained, first peak due to PVK near 450 nm and second peak due to CdS near 530 nm.PL intensity decreases with increasing concentration of CdS in PVK.